2006
DOI: 10.1038/nsmb1127
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for HIV-1 neutralization by a gp41 fusion intermediate–directed antibody

Abstract: Elicitation of potent and broadly neutralizing antibodies is an important goal in designing an effective human immunodeficiency virus-1 (HIV-1) vaccine. The HIV-1 gp41 inner-core trimer represents a functionally and structurally conserved target for therapeutics. Here we report the 2.0-A-resolution crystal structure of the complex between the antigen-binding fragment of D5, an HIV-1 cross-neutralizing antibody, and 5-helix, a gp41 inner-core mimetic. Both binding and neutralization depend on residues in the D5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
181
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(191 citation statements)
references
References 50 publications
8
181
2
Order By: Relevance
“…1) focused on residues 565-581 of the NHR (numbering according to HXB2 sequence), corresponding to the prominent hydrophobic pocket of the coiled-coil (11,20), which encompasses the D5 epitope (18,19). The chimeric mimetic IZN17 consists of an engineered trimerizing and solubilizing coiled-coil (denoted IZ) scaffold fused to aa 565-581 of gp41 (16).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) focused on residues 565-581 of the NHR (numbering according to HXB2 sequence), corresponding to the prominent hydrophobic pocket of the coiled-coil (11,20), which encompasses the D5 epitope (18,19). The chimeric mimetic IZN17 consists of an engineered trimerizing and solubilizing coiled-coil (denoted IZ) scaffold fused to aa 565-581 of gp41 (16).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of the Fab fragment of one of these mAbs (denoted D5) in complex with 5-helix (19) confirmed that D5 binds to the NHR region. Interestingly, D5 binds the same conserved hydrophobic pocket of the NHR trimer (20) that was previously shown to be the target of D-peptide (15) and peptidomimetic (21,22) HIV-1 fusion inhibitors.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Such is indeed the case for C34, T20 (4), which spans part of the HR2 region and the sequence downstream (Fig. 1), and several other FI-targeting HR1 or HR2, including peptides, proteins, and small molecules (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…2, the three antibodies were found to bind to all the prostate cells tested with comparable affinity even though Herceptin shows a lower binding ability on 22Rv1 and PC-3 cells. As a negative control, an unrelated human anti-HIV IgG1 antibody (27) was tested in parallel ELISA assays and was found unable to bind to the prostate cells (data not shown), mentioned above. As shown in Fig.…”
Section: Erbb2 Levels On Prostate Cancer Cellsmentioning
confidence: 99%